2018
DOI: 10.4314/bcse.v31i3.5
|View full text |Cite
|
Sign up to set email alerts
|

Removal of basic green 5 by carbonaceous adsorbent: Adsorption kinetics

Abstract: ABSTRACT. The Eucalyptus lenceolata wood was collected from Malakand division, Khyber Pakhtunkhwa Pakistan. Chemical activation of sample was conducted for surface efficiency. Batch studies were performed to address various experimental parameters like, contact time, temperature and adsorbent dosage for the removal of dye. For elemental analysis, surface morphology and for identification of different functional groups, energy dispersive spectroscopy (EDS), scanning electron microscopy (SEM) and Fourier transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…From the spectra of crude Eucalyptus lenceoleta and extractive free straw it is confirmed that lignin is present in these samples due to the absorption at 1514 and 1604 cm -1 . The (C-O) group stretching bands were observed at 1150, 1172 and 1188 cm -1 [26,27].…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…From the spectra of crude Eucalyptus lenceoleta and extractive free straw it is confirmed that lignin is present in these samples due to the absorption at 1514 and 1604 cm -1 . The (C-O) group stretching bands were observed at 1150, 1172 and 1188 cm -1 [26,27].…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…In short basic dyes are considered one of the more challenging classes of dyes which are considered toxic colourants. As a consequence, enhanced and cost-effective technologies are required to remove them from textile effluents [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have been reported on the polymeric composite adsorbents for separating the dyes from the wastewater, doping of any of the adsorbent material in a polymeric matrix followed by carbonization and activation makes polymeric composite adsorbents [29][30][31]. At this stage, there is still a need of more investigations on polymeric composite adsorbents on dye removal to make this process more effective and commercial.…”
Section: Introductionmentioning
confidence: 99%